Molecular identification of anaerobic fungi isolated from buffalo rumen with their growth rate, cellulase enzyme activity, and fermentation products characteristics - SINTA AGUSTINA; KOMANG GEDE WIRYAWAN; SRI SUHARTI; ANJA MERYANDINI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Agustina S, Wiryawan KG, Suharti S, Meryandini A. 2022. Molecular identification of anaerobic fungi isolated from buffalo rumen with their growth rate, cellulase enzyme activity, and fermentation products characteristics. Biodiversitas 23: 6448-6455. Anaerobic fungi are essential microbes in the degradation process of feed fiber in the rumen with the ability to produce fibrolytic enzymes and rhizoids that can penetrate feed particles. The activity of cellulase enzymes in fungi is influenced by several factors such as the type of feed and livestock used as a source of isolate. Therefore, this research aimed to analyze the types of anaerobic fungi isolated from buffalo based on their DNA nitrogenous bases composition and also to evaluate the growth rate, cellulase enzyme activity, and fermentation product concentration of anaerobic fungi. The growth rate of fungi was examined by measuring the biomass formed, while cellulase enzyme activity was carried out using CMC, Avicel, and Filter Paper as substrates. The fungal fermentation products were analyzed using the HPLC and GC methods. The results showed that the fungi isolated from buffalo rumen were closely related to anaerobic fungi type Piromyces sp., Caecomyces sp., and Neocallimastix frontalis, with different growth rate, cellulase enzyme activity, and the fermentation products concentration in each type of anaerobic fungi. Therefore, it can be concluded that anaerobic fungi isolated from buffalo rumen can degrade cellulose. It was also discovered that fungi Neocallimastix frontalis had a higher growth rate, cellulase enzyme activity (CMCase, avicelase, and FPase), and fermentation products than Piromyces sp. and Caecomyces sp.